Determinants of quality of assurance on sustainability reports in Sub-Saharan Africa: case of listed companies in Kenya, Nigeria, and Botswana - Gatakaa, Christine Njeri (Strathmore University, 2019)
In recent times, it is evident that consumer and investor needs are constantly evolving, so has the facts stakeholders consider essential for decision-making. Conventionally, financial data was essential in making decisions but presently, it is not adequate for company analysis and valuation thus, the rise in demand for non-financial (social and environmental) which is relevant in evaluation of risks and opportunities. The major drivers being investor pressure, regulation and stock exchange requirements. In response to this kind of pressure, companies seek assurance services for additional credibility and validity on the information included in their sustainability reports. Thus, this research wanted to ascertain the quality of assurance on SRs and to understand what the determinants of quality are. The study also sought the perspective of industry players on the barriers of quality assurance. Using a sample of 34 companies, 18 companies in Kenya, 9 in Nigeria, and 7 in Botswana for the period 2013 to 2017, the study findings indicate that the quality of assurance is relatively low in Sub-Saharan Africa. An evaluative framework was used to measure quality of assurance and Botswana ranked highest followed by Kenya and Nigeria. Industry sector and company profitability were the two significant variables determining the quality of assurance. From the primary data, independence of assurer, profession of assurer and the assurance engagement lead in determinants of quality of assurance on sustainability reporting. The overall findings indicate that there is a need for proper guidelines for sustainability reporting essentially improving on the quality of assurance as the assurance process can be comparable and take into consideration the material aspects in SR.
A thesis submitted in partial fulfilment of the requirement for the Degree of Master of Commerce at Strathmore University
Keywords: Sub-Saharan Africa; Listed Companies; Kenya; Botwana